ANALISIS KRIMINOLOGIS PELANGGARAN ODOL KENDARAAN ANGKUTAN BARANG DI UPPKB PADANG ULAK TANDING BENGKULU - Abdillah, Rexzy (Law Journal (LAJOUR), 2026)
Overdimension and overloading (ODOL) violations in freight transport vehicles constitute a serious problem within Indonesia’s land transportation system, as they cause road infrastructure damage, traffic safety risks, and state financial losses. Within the jurisdiction of the Motor Vehicle Weighing UPPKB Padang Ulak Tanding, Bengkulu Province, ODOL violations continue to occur frequently despite ongoing supervision and enforcement efforts. This study aims to conduct a criminological analysis of ODOL violations, identify the factors contributing to their occurrence, and examine the mitigation measures undertaken by the UPPKB Padang Ulak Tanding. This research employs a normative-empirical legal research method using statutory, case, and conceptual approaches. Data were collected through interviews with the Head of the UPPKB, Civil Servant Investigators (PPNS), and freight vehicle owners, supported by field observations and literature studies. The data were analyzed qualitatively. The findings indicate that ODOL violations constitute deviant behavior carried out consciously and repeatedly, driven by economic considerations, operational cost burdens, weak structural supervision, the low effectiveness of sanctions, and a permissive legal culture. The mitigation measures implemented by the UPPKB include preventive, repressive, and coordinative actions; however, these efforts have not been optimal due to limitations in facilities, authority, and the lack of an integrated supervisory system.